Design & cultura: representações sociais nos frascos de perfume do início do século XXI - França, Maureen Schaefer (2011)
The present studies look for reflections about the relationship between design and culture, present in the perfume bottles produced between 2000 and 2010. The purpose is to understand some social representations builted by the design of perfume bottles and their relations about the creation of spaces for the identification of potential consumers. Tried to study the packages on its materiality, how they constituted and are constituted by sócio-cultural speeches, questioning or reproducing stereotypes, traditions, social conventions and power relations. For this, was analyzed the tactile and visual language of several packages of perfume aimed at various audiences: female, male, wealthy or not, preferring those for adults, because they are in greater quantity. A semiotic analysis was used to deepen the reading of social representations from a small sample of perfume bottles, trying to show the intertwining of aesthetic, practical and symbolic functions. These packages usually give visibility to types of femininity and masculinity and lifestyles, which are crossed by gender, generational and class categories. Perfume bottles, as well as other products of design, allow to observe part of the representation of contemporary society.